(untitled) (Research, Society and Development, 2021)
The main purpose of this study was to describe the caregivers’ knowledge regarding the performance of bed bathing in a Long-term Institution for the Elderly. It was characterized as a descriptive exploratory study that was conducted in 2017, in a municipality of Ceará. The data were obtained through semi-structured interviews and interpreted according to content analysis. The results were presented and discussed through three categories that originated according to the responses of the participants, namely: 1. Scientific knowledge as the basis for carrying out the work of the caregiver; 2. The bedside bathing technique and materials used by caregivers; 3. Bath providing comfort and well-being to the client.From the results found it can be concluded that the caregivers dominate considerable part of the technique of bedside bathing, however, some necessary aspects were not covered by them. These aspects not addressed by caregivers, when allied to institutional problems such as lack of materials for hygienization harm the quality of the procedure.